Evolution of female choice in the bank vole - Horne, Taina (1998)
The aim of this thesis was to test some of the theories proposed to explain the evolution of female choice using the bank vole (Clethrionomys glareolus) as the study species. First I conducted a lab experiment to test whether female bank voles show mating preferences on the basis of male urine marking behaviour, which also indicates social status. When male-male competition was excluded, females strongly preferred dominant males but showed no clear preferences if the males where matched for urine marking behaviour. To investigate if male attractiveness is related to fertilizing ability I studied a number of variables reflecting sexual competence in relation to male urine marking value (UMV), but found little evidence for possible direct benefits of mate choice in terms of fertility. Genetic models of sexual selection assume some heritability of the sexually selected male traits. I estimated heritabilities for male UMV and three morphological traits correlated with it using parent-offspring regression. All traits had relatively high heritability values (0.53-0.77) and coefficients of additive genetic variance. To test the idea that sexually selected male traits indicate male genetic quality providing females indirect benefits through offspring fitness I studied components of offspring fitness in relation to male UMV. A laboratory breeding experiment revealed a positive relationship between male UMV and offspring body mass. In order to examine the role of differential maternal investment being responsible for this relationship I conducted a cross-fostering experiment. The results suggested that although females may invest more on offspring of attractive males, male UMV appears to indicate male genetic quality. I studied offspring performance also in natural environment and found that male UMV appears to affect some offspring fitness components. However, the study showed how difficult it is to estimate the net benefits of mate choice to the female due to trade-offs between fitness components and environment-by-genotype interactions. The studies described in this thesis support the idea of genetic mechanisms operating in the evolution of female choice. However, there are several other mechanisms, yet to be tested, and much more work is needed to understand the relative importance of each.